“Stay at Home, Obey Sunnah”: Construction of Women's Piety Through QS. al-Ahzab verse 33 in TikTok Social Media Post - Putri Ghoida’ Habibillah; Miski Miski (Religia, 2022)
This research aims to analyze the construction of women's piety through QS al-Ahzab verse 33 on social media TikTok. In tracing this construction of piety, the main question is: how is the verse visualized with a certain understanding? and what are the implications in the context of religious patterns in Indonesia? With a netnographic approach and three analytical models, such as descriptive, critical, and correlative, this research shows that QS. al-Ahzab verse 33 in the TikTok is visualized with symbols showing the domestication of women at home by playing sound, text on video, captions, and relevant videos. In this case, there are four specific important findings. First, understanding related to QS. al-Ahzab verse 33 is synonymous with an understanding based on the reasoning in translation, not on text or sources. Second, the various posts related to this theme are partly directed toward financial interests. Third, there is an attempt to confirm the identity of a group which automatically eliminates the truth of another group's version. Fourth, a new structuring structure is created in TikTok's social interactions, namely digital piety.